Analisis Yuridis Tentang Unsur – Unsur Tindak Pidana Pencucian Uang (TPPU) yang Dilakukan oleh Jaksa dalam Praktik Peradilan - Yose Sitompul; Roida Nababan (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
The criminal justice system in Indonesia is very concerned about money laundering crimes that continue to grow along with technological advances and the complexity of modern economic crimes. This study examines in depth the legal provisions related to TPPU in Indonesia, which is based on Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes. This research aims to identify the role of prosecutors as law enforcers in applying elements of anti-trafficking at the investigation and prosecution stages, as well as to analyze various obstacles that arise in the evidentiary process in court. Using a normative juridical approach, this study utilizes literature analysis, court decision review, and evaluation of relevant legal provisions. The findings of the study show that proving preliminary crimes and the flow of funds from crimes requires public prosecutors to have a comprehensive understanding of money laundering mechanisms, including the placement, layering, and integration stages. In practice, prosecutors face various challenges, such as difficulties in tracing the origins of assets disguised through complex transactions, limited access to financial technology data, and lack of cooperation support between law enforcement and financial institutions. These obstacles often cause the proving process to be protracted and less effective. Therefore, it is necessary to increase the capacity of law enforcement officials, strengthen coordination between agencies, and use more optimal technology to support efforts to eradicate trafficking more effectively and comprehensively.